Spectroscopic Properties of Yb3+/Nd3+ Co-doped Ions in SiO2-Al2O3-Na2CO3-SrF2-CaF2 Oxyfluoride Glasses for Photonic Applications - G, Umamaheswar; Gelija, Devarajulu; V, Ramaswamy; Borelli, Deva Prasad Raju (Photonics Letters of Poland, 2018)
The Yb3+ and Yb3+/Nd3+ co-doped SiO2-Al2O3-Na2CO3-SrF2-CaF2 oxyfluorosilicate glasses have been prepared by high temperature melt-quenching method. The prepared glasses are excited with 808 nm, and the near infrared emission bands are observed. The intensified emission band was centered at 1030 nm (2F5/2 -> 2F7/2) of Yb3+ ions. Stimulated emission cross-section was evaluated for the prominent 2F5/2 -> 2F7/2 transition of Yb3+ ion by using the Mc-Cumber theory. The energy transfer from Nd3+ to Yb3+ ions in co-doped silicate based oxyfluoride glasses are described under the 514 nm excitation wavelength. Full Text: PDF References N. Chiodini, A. Paleari, G. Brambilla, E. R. Taylor, "Erbium doped nanostructured tin?silicate glass?ceramic composites", Appl. Phys. Lett. 80, 4449 (2002). CrossRef D. Jaque, J. Capmany, F. Molero, Z. D. Luo, J. G. Sole, "Up-conversion luminescence in the Nd3+:YAB self frequency doubling laser crystal", Opt. mater. 10, 211 (1998). CrossRef H. Lin, G. Meredith, S. Jiang, X. Peng, T. Luo, N. Peyghambarian, E. Yue-Bun Pun, "Optical transitions and visible upconversion in Er3+ doped niobic tellurite glass", J. Appl. Phys. 93, 186 (2003) CrossRef Atul D. Sontakke, K. Annapurna, "Phonon assisted effective non-resonant energy transfer based 1 ?m luminescence from Nd3+?Yb3+ codoped zinc?boro?bismuthate glasses", J. Lumin. 138, 229 (2013). CrossRef F. Liegard, J.L. Doualan, R. Moncorge, M. Bettinelli, "Nd3+ ? Yb3+ energy transfer in a codoped metaphosphate glass as a model for Yb3+ laser operation around 980 nm", Appl. Phys. B 80, 985 (2005) CrossRef A. Miguel, B. Fan, R. Balda, X. Zhang, J. Fernandez, J.L. Adam, "Spectroscopy and energy transfer in Nd3 +/Yb3 + codoped chalcohalide glasses", J. Non-Cryst. Solids 377, 110 (2013). CrossRef G. Devarajulu, B. Deva Prasad Raju, "Effect of concentration variation on 2.0 ?m emission of Ho3+-doped SiO2?Al2O3?Na2CO3?SrF2?CaF2 oxyfluorosilicate glasses", App. Phy. A, 124 (2018). CrossRef Radoslaw Lisiecki, Elzbiecta Augustyn, Witold Ryba-Romanowski, Michal Zelechower, "Er-doped and Er, Yb co-doped oxyfluoride glasses and glass?ceramics, structural and optical properties", Opt. Mater. 33, 1630 (2011). CrossRef G. Chen, Q. Zhang, G. Yang, and Z. Jiang, "Mid-Infrared Emission Characteristic and Energy Transfer of Ho3+-Doped Tellurite Glass Sensitized by Tm3+", J. Fluoresc. 17, 301 (2007). CrossRef D. E. McCumber, "Theory of Phonon-Terminated Optical Masers", Phys. Rev. 134, 299 (1964). CrossRef D.L. Deloach, S.A. Payne, L.K. Smith, W.L. Kway, W. F. Krupke, "Laser and spectroscopic properties of Sr5(PO4)3F:Yb", J. Opt. Soc. Am. B 11, 269 (1994). CrossRef K. Venkata Krishnaiah, R. Rajeswari, K. UpendraKumar, S. Surendra Babu, I.R. Martin, C.K. Jayasankar, "Spectroscopy and radiation trapping of Yb3+ ions in lead phosphate glasses", J.Quant. Spect. Rad. Trans. 140, 37 (2014). CrossRef